High-Intensity Drug Use and Health Service Access Among Street-Involved Youth in a Canadian Setting. (6th December 2015) - Phillips, Mark; Richardson, Lindsey; Wood, Evan; Nguyen, Paul; Kerr, Thomas; DeBeck, Kora
Abstract : Background/Objectives: Addiction severity has been associated with numerous social- and health-related harms. This study sought to examine the prevalence and correlates of high-intensity drug use among street-involved youth in a Canadian setting with a focus on high-risk drug use practices and health service access. Methods: Data were derived from the At-Risk Youth Study, a Vancouver-based prospective cohort of street-involved youth aged 14–26. We used generalized estimating equations to examine variables associated with high-intensity drug use, defined as daily use of crack cocaine, cocaine, heroin, or crystal methamphetamine. Results: From September 2005 to November 2012, of 1017 youth included in the analyses, 529 (52%) reported high-intensity drug use as defined above at least once during the study period. In a multivariate analysis, older age (Adjusted Odds Ratio [AOR] = 1.47); residing in the Downtown Eastside of Vancouver (AOR = 1.46); homelessness (AOR = 1.30); recent incarceration (AOR = 1.25); inability to access addiction treatment (AOR = 1.42); and crack pipe sharing and/or used syringe injecting (AOR = 2.64), were all positively and independently associated with high-intensity drug use ( p < 0.05). The most common barrier to accessing addiction treatment reported by these youth was long waiting lists. Conclusions: High-intensity drug use among street-involved youth was prevalent and associated with structural and geographical disadvantages in addition to high-risk drug administration practices. Youth reporting more frequent drug use also reported barriers to accessing addiction treatment, highlighting the need to expand addiction services tailored to youth at greatest risk of harm from illicit drug use and street-involvement.